Pelatihan Pemanfaatan Digitalisasi Koperasi dan Pengelolaan Laporan Keuangan - Susantira Katuruni, dkk, Innas (LPPM Universitas Koperasi Indonesia, 2024)
KPRI ISI Surakarta is a cooperative whose members are all ISI Surakarta Civil Servants and has several business units, namely shops, coffee shops (Kopi Paseban), savings and loan units. KPRI ISI Surakarta has assets of more than 26 billion rupiah in 2023 has won several awards as a cooperative in the last few years and has an AAA rating. The coffee shop (Kopi Paseban) is one of the business units at KPRI ISI Surakarta, where this unit provides cafe services in the form of quality coffee and non-coffee drinks, equipped with meeting facilities and co-working space for cooperative members and the general public. Even though the coffee shop (Kopi Paseban) has very high assets and has been awarded as the best cooperative in Surakarta for several periods. The coffee shop (Kopi Paseban) cannot yet market it by implementing or making maximum use of social media, so the coffee shops (Kopi Paseban) have not been able to expand their market reach. Due to the significant increase in income and the ownership of quite a lot of assets, it is felt necessary for the cooperative to pay attention to the preparation of its financial reports. Apart from the coffee shop unit, there are shop units that require assistance or assistance to carry out records correctly to support the financial reporting of KPRI ISI Surakarta.